An in vitro study on the effect of bevacizumab on endothelial cell proliferation and VEGF concentration level in patients with hereditary hemorrhagic telangiectasia - Sadick, Haneen; Schäfer, Elena; Weiß, Christel; Rotter, Nicole; Müller, Cornelia Emika; Birk, Richard; Sadick, Maliha; Häussler, Daniel (Experimental and Therapeutic Medicine, 2022)
Previous studies have demonstrated that vascular endothelial growth factor (VEGF) is upregulated in patients with hereditary hemorrhagic telangiectasia (HHT). The use of Bevacizumab as an anti‑angiogenic treatment agent seems promising. The purpose of the present in vitro study was to determine the efficacy and potential toxicity levels of bevacizumab on cell proliferation and VEGF concentrations in endothelial cells of HHT patients. In this in vitro study, endothelial cells from patients with HHT and HUVECs (control) were incubated with different concentration levels of bevacizumab (2, 4, 6, 8 or 10 mg/ml). After 24, 48 or 72 h, the cell proliferation was assessed by Alamar Blue® Assay and the VEGF levels in the cell culture supernatants were measured by VEGF‑ELISA. All endothelial cells incubated with bevacizumab showed an initial decrease in cell proliferation. Cell proliferation recovered within 72 h in cell cultures incubated with concentration levels of up to 4 mg/ml bevacizumab, whereas those incubated with higher concentration levels showed a continuous decline in cell proliferation. VEGF expression decreased after 24 h in cell cultures incubated with bevacizumab concentration levels of 2 and 4 mg/ml but increased again after 48 h. Cell cultures incubated with bevacizumab concentration levels of 10 mg/ml showed a constant decline in VEGF expression without any tendency for recovery. Translating these results into daily clinical practice, the present study suggests that the intranasal submucosal injection of bevacizumab in HHT patients should not exceed a concentration level of 4 mg/ml. Overall, higher bevacizumab concentration levels not only reduce VEGF expression but pose a higher risk of toxic effects on endothelial cells as they jeopardize cell proliferation.
Online veröffentlicht: 5. Juli 2022
Im Titel ist "in vivo" kursiv gedruckt
Gesehen am 02.10.2023